Perencanaan dan Evaluasi Sistem Penyulang Ganda Sebagai Backup Power Supply PT. X - Muhammad Fahmi Hakim; Ahmad Hermawan; Habib Priyo Budianto; Yudistiro Yanuarianto (Elposys: Jurnal Sistem Kelistrikan, 2024)
In order to meet the needs of electrical energy, PT X. receives electricity supply from PLN as the main source while the generator with a total capacity of 2.228,5 KVA as a backup electricity supply. PT X plans to procure a double feeder as a backup power supply to replace the generator set in the hope of getting a more economical backup power supply. So, the purpose of this study are analyzing the planning and technical calculations for the construction of a premium feeder, analyzing the comparisono f the use of generator setting with double feeder from economic point of view, and analyzing the comparison of the efficiency of using generator setting with the use double feeder. The method used in this study was the IRR (Internal Rate of Return) method to determine the value of the rate of return on investment while the SAIDI – SAIFI data was used to determine the reability of the feeder. The result of this research is the double feeder using MVTIC type construction. For Rp/kWh, the use of premium service, namely B3/TM customers is Rp. 1.162,78 per kWh and B2/TM Rp. 1.574,7 per kWh, while Rp/kWh generator setting is Rp. 4.003 per kWh. Meanwhile the double feeder IRR values is 44% and the generator setting is 24%. So, it is more efficient to use PLN premium service.